Dampak Kesetaraan Gender Terhadap Kinerja Organisasi: Tinjauan Literatur Sistematis pada Sektor Publik dan Swasta - Ilham Nur Ikhsan Rintaka, Muhammad (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to explore the impact of gender equality on organizational performance, both in the public and private sectors, through a Systematic Literature Review (SLR) approach. Despite the increasing participation of women in the workforce, structural barriers such as the glass ceiling phenomenon and gender disparities in access to resources remain significant challenges. This study identifies 20 relevant articles from 120 articles analyzed, showing that gender equality has a positive impact on service quality, employee well-being, organizational innovation, and sustainability. However, the representation of women in leadership positions remains limited, especially in countries with strong patriarchal cultures. Additionally, gender quota policies in the academic and political sectors have been shown to improve female representation, though structural barriers and gender stereotypes persist. The findings of this study provide valuable insights for decision-making at both organizational and public policy levels in designing more inclusive and sustainable measures. Therefore, gender equality is not only ethically important but also a strategy for enhancing organizational performance in the long run.